Agrotóxicos em milho: otimização e validação de método multirresíduo empregando GC-MS/MS - Facco, Janice de Fátima (2013)
Due to the complexity of its matrix, more efficient methods have been studied for the determination of pesticide residues in maize. The use of QuEChERS method coupled to low temperature clean up technique has showed advantages to reduce lipids during sample preparation in matrix with high fat content. It was optimized and validated in this study a multiresidue method for the determination of pesticides in maize employing QuEChERS and GC-MS/MS. The extraction procedure was optimized though the factorial design, and consisted in weighing 2.5 g of sample and adding 10 mL of ultrapurified water followed by vortex shaking for 1 min. After this, It was added 10 mL of acetonitrile and the tube was stirred for 1 h in a platform shaker at 200 rpm. Partition step was performed using 1 g of NaCl and 6 g of MgSO4, followed by manual shaking for 1 min and centrifugation at 3400 rpm for 8 min, at 10 ºC. An aliquot of 4 mL of the extract was transferred to a 15 mL tube for clean up step at low temperature for 12 h around -20 ºC. Finally, another clean up stage was realized applying dispersive SPE, 1 mL of the extract was transferred to a tube containing 150 mg of MgSO4, 50 mg of C18 and 50 mg of PSA followed by shaking and centrifugation. The final extract was filtered and analyzed by GC-MS/MS. Analytical parameters evaluated in this work were linearity of the analytical curve, limit of detection (LOD), limit of quantification (LOQ), precision, accuracy and matrix effect for the 12 compounds studied. The method showed efficient, with recovery results in a range of 55.3 to 110.1% in the spiked levels of concentration of 40, 100 and 200 μg kg-1 and RSD ≤ 20%. Values of instrument LOD and LOQ were 1.5 and 5.0 μg L-1, respectively. Method LOQ was 100 μg kg-1 for most compounds. Thereby, It was concluded that the proposed method demonstrated to be adequate for the analysis of most pesticide residues studied in maize, since the parameters evaluated were in according to the limits required for chromatographic methods validation applied in residues analysis.